Evaluation of Vitamin D Status among Populations in Tobruk City, Libya - Fathia Bougafa; Rema Tahir (AlQalam Journal of Medical and Applied Sciences, 2021)
Background. Vitamin D deficiency (VDD) has pandemic proportions worldwide. Numerous studies have reported high prevalence of VDD in the sunniest areas of the world, such as Near East and North Africa (NENA) including Libya. To contribute to the body of evidence, measurement of vitamin D status on Libyan population at Tobruk region was conducted. Methods. A total of 568 cases (169 males and 399 females) aged 0 to >40 years were tested for vitamin D level. Serum 25(OH)D was analysed using ECLIA assay by Cobas machine e 411. The associations of the levels of 25(OH)D3 with gender, and age groups were assessed throughout using the Chi-square test on SPSS software. Results. The results showed that the participants with VDD (< 20 ng/L) recorded the highest percentage (52.1%), followed by those with insufficient level (20-50ng/L) (46.3%) while those with high level or adequate (> 50 ng/L) were found the lowest percentage (1.6%). The results revealed a significant correlation (X2=23.28; P<0.01) between the age group and vitamin D level. Moreover, the results revealed that the youngest participants (0–20 years) recorded the highest percentage (59.3%) of optimum level of vitamin D, while those oldest ones with age group as 21-30 years, 31-40 and >40 years have the highest frequencies (60.6, 56.2 and 57.5% respectively) of low level of vitamin D. The results revealed that more than half of population in Tobruk city may have low vitamin D level. Conclusion. The situation calls for multi-sectoral actions and public health initiatives to address dietary and lifestyle habits. sunlight exposure may enhance vitamin D level.